2001
DOI: 10.1016/s0735-1097(01)01301-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human recombinant vascular endothelial growth factor165on progression of atherosclerotic plaque

Abstract: Recombinant human VEGF increases the rate and degree of atherosclerotic plaque formation in the thoracic aorta in a cholesterol-fed rabbit model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 19 publications
2
64
1
Order By: Relevance
“…24 Another potential complication is the administration of angiogenic cytokines may promote the neointimal thickening and accelerate atherosclerosis by angiogenic stimuli on vasa vasorum of the artery wall. [25][26][27][28] So far, the clinical trials refute the idea that angiogenesis therapy stimulates tumor growth; however, animal studies have demonstrated that VEGF significantly enhances intimal thickening. [25][26][27][28] Since obesity is one of the major risk factors for atherosclerosis and coronary artery disease, the angiogenic status in overweight subjects without diabetes, hypertension, hyperlipidemia, and ischemic heart disease was evaluated in this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another potential complication is the administration of angiogenic cytokines may promote the neointimal thickening and accelerate atherosclerosis by angiogenic stimuli on vasa vasorum of the artery wall. [25][26][27][28] So far, the clinical trials refute the idea that angiogenesis therapy stimulates tumor growth; however, animal studies have demonstrated that VEGF significantly enhances intimal thickening. [25][26][27][28] Since obesity is one of the major risk factors for atherosclerosis and coronary artery disease, the angiogenic status in overweight subjects without diabetes, hypertension, hyperlipidemia, and ischemic heart disease was evaluated in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in animal studies, there are still controversies whether it reduces intimal thickening by accelerating re-endothelialization 34 or enhances intimal thickening. [25][26][27][28] In preadipocytes in culture, bFGF stimulates the replication and inhibits their differentiation 10 and the expression of bFGF decreases during adipocyte differentiation 11 . In fully matured adipocytes, the addition of a high concentration of bFGF into culture media induces the reversal of adipocyte differentiation 12 and marked suppression of activity of GPDH 13 .…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, treatment with VEGF stimulates plaque angiogenesis and promotes lesion progression both in ApoE À/À mice and in cholesterol-fed rabbit models. 43 There is a notable dearth of knowledge about the signaling processes that link ROS, angiogenesis and neointimal lesion formation. For instance, overexpression of the NADPH oxidase subunit, p22 phox has been shown to increase HIF-1a, VEGF expression and intralesional angiogenesis and to promote experimental atheroma progression.…”
Section: Disscussionmentioning
confidence: 99%
“…26,27 A possible link between increased plasma levels of VEGF and the development of cardiovascular disease is discussed after two reports showed that administration of VEGF in mice and rabbits induced the progression of atherosclerotic plaques. 28,29 It should be mentioned, however, that the impact of adipose tissue VEGF to the serum VEGF level is still controversially discussed. Here we show that the inflammatory mediators IL-6 and OSM upregulate the expression of VEGF in human and murine adipose tissue and Figure 5.…”
Section: Rega Et Al Vegf Regulation By Cytokines In Adipose Tissuementioning
confidence: 99%